Exploring the relationship between the pre-service teachers’ nature of TSPCK acquired in planning and that enacted in classroom practice - Zondi, Mpumelelo Faith (My University, 2018)
This study explored the relationship between the physical science pre-service teachers’ nature of topic specific pedagogical content knowledge (tsPCK) acquired in planning and that enacted in the classroom teaching of stoichiometry. The research study was based on the construct of tsPCK developed by Mavhunga (2012) as it focused on the knowledge required for transforming the content knowledge of a specific science topic. The study was performed on three groups of fourth year pre-service teachers doing a physical science methodology course at a university in South Africa. There were 12 participants in total. Collected data included the lesson plans, video-recordings of microteaching, and reflection reports; all done by the participant pre-service teachers in the stoichiometry. The research used an in-depth qualitative method to analyse the results by looking for possible moments of integration of tsPCK components represented by tsPCK maps. The validated tsPCK rubric was used to quantify the observed tsPCK episodes and describe the quality of tsPCK. An analysis of the collected data revealed that even though there was a relationship in terms of components in the lesson plans and enacted lesson, the enacted lessons had a better quality than the lesson plans. It was also observed that most of the enacted lessons were interwoven and had more knowledge components of tsPCK than the lesson plans. The implications of the study were discussed.
A Research Project submitted to the Faculty of Science, University of the Witwatersrand In partial fulfilment of the requirements for the degree of Masters in Education, Johannesburg 2018
Keywords: Pedagogical content knowledge--South Africa; Science teachers--South Africa; Science--Study and teaching (Higher)--South Africa